De la Bourgogne à la Syrie, et retour : Orientalisme et régionalisme dans l’œuvre d’Alice Poulleau - Élodie Gaden; Pascale Roux (Viatica)
This article concentrates on the work of Alice Poulleau, a young female traveller from the beginning of 20th century who defended the freedom of peoples to self-determination and who developed a critical view of Western actions. The study, which focuses on the writer’s travel journal À Damas sous les bombes, her Eastern stories Sept histoires de Syrie and La Madone, as well as her Burgundy stories Pur jus: Faicts et dicts de biberons de Borgoingne, analyses the place of the traveller’s experience at the heart of her fiction and examines the tangible link between the writer’s place of origin (Burgundy) and the East of her travels.